Tinjauan Kritis Kerangka Kerja Pengkajian Filsafat Islam Pada Buku ‘History of Philosophy in Islam’ Karya T.J. De Boer: A Critical Review of the Study of Islamic Philosophy Framework's: An Analysis of the book History of Philosophy in Islam by Tjitze Jacobs de Boer - Ahmad Rizqi Fadlilah (Journal of Islamic and Occidental Studies, 2023)
In the study of Islamic philosophy, De Boer is a representative figure and is considered his thought. His work entitled History of Philosophy in Islam is the first writing that is compiled holistically from the initial period of the formation of Islamic philosophy to the Medieval Period. This paper tries to read De Boer's thoughts in his work and critically analyze the framework he uses. This paper is qualitative in nature by taking the text as its data source, which is analyzed descriptively-critically with a philosophical and historical approach. In his work, De Boer chose "philosophy in Islam" as a term for the tradition of critical thinking in Islamic civilization. With this designation, Muslim philosophers are those who have philosophical thought in Islamic history, with al-Farabi as the originator. According to De Boer, philosophy in Islam is limited to the paripathetic tradition. De Boer's choice of the term "philosophy in Islam" shows his doubts about the authenticity of Islamic philosophy, so that Muslim philosophers only continued the Greek tradition of thought. This frame of mind is typical of Western orientalists. This paper discovers the confusion in De Boer's thinking and proves that the tradition of Islamic thought, Islamic sciences, including Islamic Philosophy, has existed since the beginning of Islam and is original based on the unique Islamic worldview.